(untitled) (Journal of Parents and Teachers, 2026)
Whether positive or negative, what educators assess in everyday life is: activity, feeling and consistency. No one learns in the same way, and this is something that teachers must be very clear about. On the other hand, educational reform is paving the way for music, both in primary education, within arts education, and in compulsory secondary education, as a specific and independent subject. Music will surely have a place in schools, which will bring countless benefits for students.